Electoral engineering in the case of political instability - Макаренко, А. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with the concept of the electoral engineering in the conditions of state's political instability. The specificity of elections in countries with no stable political system and/or which are in process of transition from authoritarianism is defined. The distinction between electoral rules that help to replace or contribute to maintain the existing power is analyzed.  The directions of using electoral engineering to prevent political violence and deadly conflicts in the conditions of political instability are described.